Hibah Pemerintah dan Pertanggungjawabannya - Prastowo Budi; M. Hari Wahyudi; A’an Effendi (Justitia Jurnal Hukum, 2017)
Government grant is one of the legal acts of the Government in the distribution of welfare of citizens. The purpose of this study is to determine the government that does not grant its designation that an act of corruption as well as the withdrawal of government grants if there are irregularities. The research method uses a normative juridical approach statute and case approach. The results of research in writing this law first: the incompatibility of the proposed treaty grants the user an act of corruption. The results of the second study: Government grants that have been given by the Government to grant recipients may be withdrawn if there is deviation to make legal effort to administrative sanctions, civil or  criminal.Keywords: Grants, Government, Corruption